Resepsi Hermeneutika Visual Dalam Karakter Xiao Di Game Genshin Impact - Adi Saskara, I Putu; Ida Bagus Komang Sindu Putra; SM, Ulio (UHN IGB Sugriwa Denpasar, 2024)
Video games are an entertainment phenomenon that is popular among today's people. Various genres of video games have emerged and have their own impression on the players. In it, video games have visual elements that have their own uniqueness and aesthetic value. These visuals can provide information, especially on the character designs in the game world. Like the visual elements in the game Genshin Impact, where the visual elements in it certainly have meaning and interpretation of each other and form the narrative in the game itself. Characters created with certain characteristics will certainly attract players' interest. This research aims to interpret the visual design contained in the creation of a character using Ricoer's hermeneutic theory. Through analysis carried out with Ricoer's visual hermeneutics perspective, we can view Xiao's character design as a work of art that is not only pleasing to the eye, but also summarizes a philosophical and emotional narrative that gives character depth in this fantasy world. Hermeneutics plays a central role in helping us understand the meaning and complexity of Xiao's character behind his visual elements.